Influence of the Angle of Irradiation of the Er,Cr:YSGG Laser on the Morphology, Attachment of Blood Components, Roughness, and Root Wear: In Vitro Study - Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Pavone, Chaine [UNESP]; Cezar Sampaio, Jose Eduardo [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Wiley-liss, 2010)
Background and Objectives: To evaluate the influence of the working tip angulation of the Er,Cr:YSGG laser on the morphology, attachment of blood components, roughness, and wear on irradiated root surfaces compared to scaling and root planing (SRP).Study Design/Materials and Methods: The present study used 45 teeth, of which 25 were used for the analysis of the morphology and the attachment of blood components and 20 were used for the analysis of the roughness and of the root wear. The teeth were randomly divided into five groups according to the treatment applied: (G1) Laser Er,Cr:YSGG-30 degrees; (G2) Laser Er,Cr:YSGG-45 degrees; (G3) Laser Er,Cr:YSGG-60 degrees; (G4) Laser Er,Cr:YSGG-90 degrees; and (G5) SRP.Results: The root surfaces irradiated with the Er, Cr: YSGG laser working angulation tip of 45 degrees and 60 degrees, and the samples scaled with manual instruments presented greater attachment of blood components than the group where the Er, Cr: YSGG laser irradiated at working tip angulation of 30 degrees and 90 degrees (P<0.05). The samples irradiated with the Er, Cr: YSGG laser were rougher than the samples scaled with manual instruments (P<0.05). The group that was irradiated with the Er, Cr: YSGG laser at an angle of 30 degrees presented the least wear in comparison to all the other treatments (P<0.01).Conclusions: The irradiated root surfaces proved to be rougher than those scaled with manual instruments; however, irradiation at working tip angulations of 45 degrees and 60 degrees produced results of attachment of blood components and root wear comparable with those obtained with manual instrumentation. Lasers Surg. Med. 42:683-691, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: dental scaling; lasers; periodontitis; regeneration